THE ROLE OF STEM EDUCATION IN DEVELOPING MODERN SKILLS ESSENTIAL FOR STUDENTS’ LIVES - Ergasheva Muqaddas Toshtemirovna (Bright Mind Publishing, 2025)
This article examines the critical role of STEM (science, technology, engineering, and mathematics) education in developing the 21st century skills needed to succeed in the modern world. It argues that STEM-based education not only strengthens students’ knowledge in scientific and technical fields, but also develops important soft skills such as critical thinking, creativity, collaboration, and communication. The integration of STEM subjects develops problem-solving skills and prepares students to adapt to a rapidly changing technological environment. It also discusses how STEM education fosters innovation, digital literacy, and lifelong learning, which are critical for building a competitive and sustainable society in an era of globalization.
Keywords: STEM education, innovation, digital literacy, creativity